Cesar Chavez - Peña, Michael 1976-; Ferrera, America 1984-; Dawson, Rosario 1979-; Luna, Diego 1979-; Pearson, Keir (Pantelion, 2014)
The story of the famed civil rights leader and labor organizer torn between his duties as a husband and father and his commitment to securing a living wage for farm workers. Chavez embraced non-violence as he battled greed and prejudice in his struggle to bring dignity to people. He inspired millions of Americans who never worked on a farm to fight for social justice. His triumphant journey is a remarkable testament to the power of one individual's ability to change the world
USA, 2013
Keywords: Chavez, Cesar / 1927-1993 / Drama; Chavez, Cesar -- 1927-1993 -- Drama; Chávez, César -- 1927-1993; United Farm Workers / Drama; United Farm Workers -- Drama; United Farm Workers; Labor leaders / United States / Drama; Migrant agricultural laborers / Drama; Mexican American migrant agricultural laborers / Drama; Civil rights workers / Drama; Labor leaders -- United States -- Drama; Migrant agricultural laborers -- Drama; Mexican American migrant agricultural laborers -- Drama; Civil rights workers -- Drama; Feature films.; Video recordings for the hearing impaired.; Chicanos; Landarbeiter; USA; DVD-Video